Twenty Years of Data on China's Africa Lending - Kevin Acker; Deborah Brautigam (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2021)
China's lending to Africa remained significant in 2019, but its nature is changing. Chinese financiers have committed US 153 billion to African public sector borrowers between 2000 and 2019. At least 80 percent of these loans financed economic and social infrastructure projects: mainly transport, power, telecoms, and water. In 2019, Chinese financiers committed US 7 billion to African borrowers, down 30 percent from US 9.9 billion in 2018. We expect this dip to continue through 2020, reflecting the impact of the pandemic and associated economic dislocation. Yet we do not predict a sustained drop in Chinese lending to Africa. Like other lenders, Chinese banks are interested in the profits available in emerging and frontier markets. - Down but not out. China's loan commitments (2000- 2019) in Africa now total US 153 billion. New Chinese loan commitments of US 7 billion dipped 30% in 2019 compared with 2018. - Avoiding risk. Countries where China reprofiled, restructured, or refinanced existing debt between 2015 and 2019, including Angola, Cameroon, Djibouti, Ethiopia, Mozambique, and Republic of Congo, received far less Chinese finance in subsequent years. In 2019, China's top borrowers were Ghana, South Africa, Egypt, Cot̂e d'Ivoire and Nigeria. - Changing creditors. In 2019, CARI data included over 30 Chinese banks and other lenders. Lending from China Eximbank, China's only source of concessional loans and preferential export credits, peaked in 2013. Commercial loans from China Development Bank and other banks have filled the gap. - Resource-backed finance is evolving. Although accounting for only 8% of total Chinese lending to Africa (aside from Angola), the controversial resource-backed infrastructure financing model is not dead; it lives on in Ghana and Guinea.
Keywords: 330